Azeotropic Distillation - Arlt, Wolfgang (Elsevier Inc., 2014)
In an azeotropic distillation process, a third component, the entrainer, is added to a binary mixture to influence the azeotropic system in such a way that collection of pure products is possible. For better understanding, first the concept of residual curves and distillation lines is introduced. These give a graphical representation of the distillation of a three-component mixture, which is always the case with azeotropic distillation. With such diagrams, the mechanism of azeotropic distillation based on the thermodynamic behavior of the three-component system can be explained.The entrainer is the added (third) component of the binary mixture that is to be separated to create a suitable azeotrope. What is "suitable" can be found by applying a priori thermodynamical tools like the conductor-like screening model for real solvents. The last section of this chapter shows the application of azeotropic distillation for the separation of ethanol and water with toluene as the entrainer in a technical process. In this process, the formation of a ternary heteroazeotrope is utilized for the separation.
Keywords: Azeotropic distillation; Conductor-like screening model for real solvents (COSMO-RS); Distillation line; Entrainer; Heteroazeotrope